Outcomes following severe hand foot and mouth disease: A systematic review and meta-analysis - Jones E. (2018)
HRvD and SS were funded by the Wellcome Trust of Great Britain ( 089276/Z/09/Z and 106680/Z/14/Z ) and a Li Ka Shing Foundation–University of Oxford Global Health Program strategic award ( LG17 ). JCBA has been awarded a doctoral scholarship by CIENCIACTIVA, an initiative of the Peruvian National Council of Science, Technology and Technological Innovation (CONCYTEC); grant contract number 231-2015-FONDECYT. HY was supported by the National Science Fund for Distinguished Young Scholars ( No.81525023 ), the National Natural Science Foundation of China ( No. 81473031 ), the Li Ka Shing Oxford Global Health Programme ( No.B9RST00-B900.57 ).